Workshop Sinergi Mendeley dan AI dalam Meningkatkan Kualitas Skripsi Mahasiswa Akhir IAI Laa Roiba Bogor - Muhamad Priyatna; Unang Wahidin; Wartono Wartono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The low quality of scientific publications and student obstacles in reference management and technology adaptation are the main challenges in the university environment. Limitations in compiling citations manually often hinder the smooth writing of the final project. This PkM activity aims to improve the competence of final students of IAIN Laa Roiba Bogor in writing quality scientific papers through the integration of the Mendeley application and the ethical use of Artificial Intelligence (AI) tools. The implementation of the activity uses a Participatory and Hands-on Training (learning by doing) approach which includes three main sessions: the basics of scientific writing, Mendeley's hands-on practice, and the optimization of AI for literature synthesis. The target of the activity is final year students of the 2025/2026 academic year. This activity succeeded in providing an in-depth understanding of the structure of scientific papers and the technical skills of using Mendeley and AI as writing assistants. Success indicators are measured through the improvement of final students' skills compared to before the activity and the production of an initial draft of scientific papers that have used automatic citations. The integration of Mendeley and AI has proven to be a strategic step in improving digital literacy and student efficiency in completing final projects according to scientific ethics rules.